Flow Analysis Of Five-Axis Impeller In Vacuum Casting By Computer Simulation - Ahmad, Mohd Nazri; Osman, Mohd Hairizal; Jumaidin, Ridhwan; Abu Hassan, Muhammad Afiq; Wahid, Mohammad Khalid; Maidin, Nurul Ain; Ab Rahman, Mohd Hidayat (Penerbit Akademia Baru, 2019)
Vacuum casting is a modern technique in the casting technology. It is capable to cast the complex parts with low tooling cost and short time. Thus, in order to achieve the optimum result of casted parts the computer simulation was used in the analysis. So, this paper presents the study to analyze the flow of resin into the mould of five-axis impeller by vacuum casting process. Computer simulation was used to define critical parameters such as casting point location, flow temperature, average, flow velocity, air traps location and filling time. The Moldflow software was used as simulation tool to gain result of analysis. Polyurethane resin has been used as raw material to cast a five-axis impeller. Vacuum casting machine types KLM 1000A was selected and mould is made by silicone rubber mould (Axson-Essil291). Otherwise, pattern for impeller was fabricated by 3D printer type's powder based which is named as Project460. The results from simulation show that the maximum flow temperature in cavity could be 230.1 degree celcius (°C), 0.142 centimetre per second (cm/s) for average flow velocity and 0.5210 second (s) for filling time. Meanwhile, the casting point location could be located at the top of the mould cavity. Therefore, by using computer simulation for flow analysis, it shows that on how the material flows in a cavity, the risk areas, the air trap forming and the suitable position for casting funnel that would be contributed to increase the quality of the part.